Penerapan metode waspas dalam penerima bantuan langsung tunai - Torang Siregar (Jujurnal Publisher, 2024)
Direct Cash Assistance (BLT) is a government program for poor communities sourced from village funds to reduce the economic impact. In implementing distribution, BLT faced many problems due to weak government supervision of this assistance. Sinunukan government VI P4HDR KM. 10, Sinunukan District, Madina Regency pays close attention to the distribution of BLT because the data obtained is still managed manually with unclear criteria and is not in accordance with the Village Ministerial Regulation. It is feared that this will lead to inaccurate assessments, so that BLT does not reach the poor people who need it most. So a system is needed that can determine BLT recipients in Sinunukan VI P4HDR KM. 10, Sinunukan District, Madina Regency objectively. In this research, the Weighted Aggregated Sum Product Assessment (WASPAS) method was applied.This system assigns a weight value to each criterion using ROC (Rank Order Centroid) weighting, namely sorting potential recipients based on the priority or level of importance of the criteria for aid recipients. This system uses the PHP and MySQL programming languages to handle the database. Meanwhile, the system output is the order of BLT recipients in Sinunukan VI P4HDR KM. 10 Village. The comparison of the results of this system with the results of BLT recipients in 2021 is 65%.